Path length and spectrum of single-cycle mid-IR light bullets in transparent dielectrics. (April 2018) - Chekalin, S.V.; Kompanets, V.O.; Dormidonov, A.E.; Kandidov, V.P.
Abstract: Filamentation of femtosecond laser radiation with a wavelength of 800 – 3900 nm and a power slightly exceeding the critical self-focusing power is studied using the spectral method and the method of laser coloration in LiF crystal. It is found that the length of a filament formed in the single-pulse regime increases with increasing excitation wavelength from a few tens of micrometres at 80 nm to hundreds of micrometres at 3900 nm. In the spectral region of anomalous group velocity dispersion, starting from 2600 nm, the initially smooth luminescence profile of the long-lived induced colour centres acquires a periodic structure, demonstrating the formation of a light bullet with a duration of about one cycle of the light field oscillation and a diameter smaller than 10 μm. The path length of such bullets does not exceed 0.5 mm in the single-pulse regime and 2.7 mm in the waveguide regime. A consequence of periodic modulation of the bullet light field in the process of propagation, observed experimentally and confirmed by calculations, is the appearance of sidebands near the excitation wavelength, as well as the appearance of visible spectral components in the supercontinuum radiation, whose angular divergence increases with increasing wavelength.